T Cell Subpopulations in Healthy Elderly and Lung Cancer Patients: Insights from Cuban Studies - Saavedra, Danay; Garcia, Beatriz; Lage, Agustin (Frontiers in Immunology, 2017)
The senescence of the immune system and the risk of cancer increase with aging. Age itself entails changes in the immune system, which are related to a decrease in thymic output of naïve lymphocytes, an accumulation of chronic antigenic load, notably chronic viral infections such as cytomegalovirus (CMV), and replicative senescence of lymphocytes. These changes could eventually contribute to cancer risk and affect the response to cancer treatment. However, several confounding factors make it difficult to draw a picture of causal relationships. Studies in diverse human populations could contribute to clarify these complex relationships. Here, we summarize the current knowledge about the senescence of the T cells, the relationship with CMV infection, cancer, and cancer treatment. We also review the results of a series of studies performed in Cuba whose population is characterized by the unusual combination of long life expectancy and high antigenic load, including high seroprevalence of CMV, typical of tropical countries. Although immunosenescence affects almost all components and functions of the immune response, its most salient feature is a decrease in numbers and proportions of naïve CD8+ T lymphocytes and an accretion of terminally differentiated CD8+ T lymphocytes. These features were confirmed by the Cuban studies, but interestingly a clear gender effect also appeared. Moreover, as aging is a global phenomenon, a fast increase in elderly with malignancies is expected; therefore, the evaluation of patient’s immune status would support the decision of treating them with immunotherapy and predict the efficacy of such treatments, thereby improving benefits for the patients.